A Building Information Model enabled Multiple Traveling Salesman Problem for building interior patrols. (January 2021) - Chen, Chun-Hao; Lee, Yu-Ching; Chen, Albert Y.
Abstract: During building emergencies, an effective and visible primary search plan enhances situation awareness and enables a more efficient rescue mission. The aim of the primary search during an emergency is the rapid screening of every space in the building to identify locations of victims and their conditions. Afterwards, first responders can plan for the rescue of those victims. To provide a timely draw up of interior patrol routes and assign rescue teams to conduct the primary search, this study formulates the problem as a multiple traveling salesman problem (M-TSP) where the comprehensive building interior network is given by the building information models (BIMs), while the total traveling costs (lengths) of every rescue team is minimized. To meet the requirement of real-time patrol routes optimization, we employed the branch-and-price algorithm for the enhancement of computation efficiency. In addition, a heuristic method was introduced to provide timely solutions for large-scale networks. A case study is conducted for a single-floor convention center. We utilized BIM to construct a network of nodes and arcs where the decision model requires as input, and the branch-and-price algorithm finds the optimal patrol. The resulting patrol routes can be visualized and serve as guide for rescue teams to conduct the primary search. The integrated approach proposed in this study is practical and can expedite search and rescue missions.